INs and OUTs of faces in consciousness: a study of the temporal evolution of consciousness of faces during binocular rivalry - Quettier, Thomas; Di Lello, Nicolò; Tsuchiya, Naotsugu; Sessa, Paola (Frontiers in Human Neuroscience, 2023)
Contents of consciousness change over time. However, the study of dynamics in consciousness has been largely neglected. Aru and Bachmann have recently brought to the attention of scientists dealing with consciousness the relevance of making inquiries about its temporal evolution. Importantly, they also pointed out several experimental questions as guidelines for researchers interested in studying the temporal evolution of consciousness, including the phases of formation and dissolution of content. They also suggested that these two phases could be characterized by asymmetric inertia. The main objective of the present investigation was to approximate the dynamics of these two phases in the context of conscious face perception. To this aim, we tested the time course of content transitions during a binocular rivalry task using face stimuli and asked participants to map their subjective experience of transitions from one content to the other through a joystick. We then computed metrics of joystick velocity linked to content transitions as proxies of the formation and dissolution phases. We found a general phase effect such that the formation phase was slower than the dissolution phase. Furthermore, we observed an effect specific to happy facial expressions, such that their contents were slower to form and dissolve than that of neutral expressions. We further propose to include a third phase of stabilization of conscious content between formation and dissolution.